Impact of out-of-home nutrition labelling on people with eating disorders: a systematic review and meta-synthesis - Lucy Serpell; Dasha Nicholls; Ulrike Schmidt; Tom Jewell; Nora Trompeter; Fiona Duffy; Imogen Peebles; Emily Wadhera; Kate Chambers; Helen Sharpe; Ellen Maloney (BMJ Public Health)
Objectives Mandatory nutrition labels for out-of-home food consumption have been introduced in several countries to curb rising obesity levels. However, concerns have been raised about the potential negative impacts of such policies on individuals with eating disorders. This review aimed to summarise the literature on the impact of out-of-home nutrition labels on individuals with eating disorders or disordered eating.Design A systematic search across eight databases was conducted on 11 October 2023.Data sources MEDLINE, EMBASE, APA PsycINFO, Web of Science, ProQuest Dissertations and Theses Global, Scopus and CINAHL. Unpublished studies were searched for on Google Scholar and PsyArXiv.Eligibility criteria Studies were included if they assessed the impact of out-of-home nutrition labelling policies on individuals with eating disorders or disordered eating.Data extraction and synthesis 538 studies were screened, of which 16 studies met inclusion criteria.Results The reviewed studies included five experimental/quasi-experimental studies, five cross-sectional studies and six qualitative/mixed-methods studies. Across studies, eating disorder pathology was associated with noticing labels more frequently, paying more attention to caloric intake and more frequent behaviour changes due to caloric values. The metasynthesis identified five themes based on the qualitative findings, being drawn to calories, facilitating the eating disorder, reassurance, social eating and frustration.Conclusions The current review summarised the existing literature on the impact of out-of-home nutrition label policies on individuals with eating disorders. The evidence suggests that there is cause for concern regarding negative impacts, particularly for those with restrictive eating disorders, which should be explored further by research and considered by policymakers when making decisions on public health policies.